Invigorasi Benih Timun Apel (Cucumis melo L.) Dengan Kombinasi Zat Pengatur Tumbuh Naa (Naphtaleine Acetic Acid) dan Ekstrak Tauge Selama Periode Pembibitan - Aan Rosita; Darso Sugiono; Elia Azizah (Peneliti.net, 2022)
The producticivity of apple cucumber plants is relatively low. One of the determining factors for the success of apple cucumber production is the quality of seeds. Invigoration is an effort that can be made to improve the quality of seeds. The study was conducted at Screen House of Kepuh Al-Jariah Village, Karangpawitan District, Karawang Regency, West Java Province in October to December 2021. The experiment designe was randomized block design (RBD) consisting with 5 replications and 7 treatments consisting of: Z0 (control), Z1 (Naphtaleine Acetic Acid (NAA) 100 ppm + bean sprouts extract 40%), Z2 (Naphtaleine Acetic Acid (NAA) 200 ppm + bean sprouts extract 40%), Z3 (Naphtaleine Acetic Acid (NAA) 100 ppm + bean sprouts extract 60%), Z4 (Naphtaleine Acetic Acid (NAA) 200 ppm + bean sprouts extract 60%), Z5 (Naphtaleine Acetic Acid (NAA) 100 ppm + bean sprouts extract 80%), and Z6 (Naphtaleine Acetic Acid (NAA) 200 ppm + bean sprouts extract 80%). The results showed that in the observation of stage 1 parameters of germinating power (DB), growth seismicity (Kst) and growth speed (Kct) had no real influence on all treatments. Meanwhile, the real influence was only found in the parameters of the vigor index. Stage 2 observations showed that the parameters of plant height, number of leaves, and number of buds had a noticeable influence. Meanwhile, the unreal influence was only found in the parameters of root length. Z2 treatment (NAA 200 ppm + 40% bean sprout extract) is the best combination that is able to provide the best response to stage 1 and 2 observation parameters. Where in stage 1 the treatment Z2 has a germination power of 96%, the vigor index is 68%, seismicity grows 92%, and the speed grows 20%. While in stage 2, the Z2 treatment has a plant height of 26,30 cm, the number of leaves is 9,48 strands, the number of buds is 7,48, and the root length is 29,45 cm.